The virtues, or, The examined life - Cessario, Romanus (Handbooks of Catholic theology., 2002)
The chief characteristic of Christian morality is its being linked to the person of Jesus Christ who is himself the universal, personal, and concrete norm of moral action. This book is about the virtues of the Christian life--both the theological virtues (faith, hope, and charity) and the cardinal virtues (prudence, justice, fortitude, and temperance)--and it deals particularly with the question, how it is possible for believers to decide for the morally good and to live accordingly. Reflecting on the basic questions of Christian morality, the book offers a commentary on the corresponding sect.